Communication—Correction Note to the Paper, “On Jockeying in Queues” - Koenigsberg, Ernest (Management Science, 1977)
In the paper “On Jockeying in Queues” (Management Science, Vol. 12 (1966), pp. 412–436) I presented erroneous results for two of the seven models examined.